Comparisons of mood states associated with outcomes achieved by female and male athletes in high-level judo and Brazilian Jiu-Jitsu championships: Psychological factors associated with the probability of success - Brandt R. (2021)
© 2019 National Strength and Conditioning Association.Brandt, R, Bevilacqua, GG, Crocetta, TB, Monteiro, CBdM, Guarnieri, R, Hobold, E, Flores, LJF, Miarka, B, and Andrade, A. Comparisons of mood states associated with outcomes achieved by female and male athletes in high-level judo and Brazilian jiujitsu championships: psychological factors associated with the probability of success. J Strength Cond Res 35(9): 2518-2524, 2019-Moods can be used to predict the performance of athletes in various sports; accordingly, we selected the Brunel Mood Scale (BRUMS) to evaluate mood states of high-level judo and Brazilian jiu-jitsu (BJJ) athletes. The aims of this study were (a) to compare the mood states of high-level female and male athletes in BJJ and judo championships in relation to their performance outcomes and (b) to verify associations between psychological factors and performance in estimating their probability of success. The subjects were 173 grappling athletes (judo, n = 85 and BJJ, n = 88), separated into male (n = 129, 40 winners and 89 nonwinners) and female (n = 44, 23 winners and 21 nonwinners) groups. Each subject's mood state was assessed 60 minutes before the first match using the BRUMS (tension, depression, anger, vigor, fatigue, and mental confusion dimensions). Descriptive and inferential statistics (including logistic regression and variance analysis) were used to evaluate relations between mood states and performance (i.e., winning/losing), with p ≤ 0.05. Analysis showed significant differences between male and female athletes in vigor and fatigue, and differences betweenmale judo and male BJJ athletes in tension, vigor, confusion, and fatigue. Female judo and female BJJ athletes showed significant differences in depression and vigor. Logistic regression revealed that higher levels of anger and tension increased athletes' chances of performing well in amatch by 23 and 13%, respectively. In addition, lower levels of depression increased athletes' chances of better performance by up to 32%. Overall, we observed a significant relationship between mood state and sports performance. Thus, coaching staff and athletes should monitor athletes' mood states before competitions to ensure that they are in optimal condition to perform and use psychological interventions to support judo and BJJ preparation.